On statistical parameters characterizing vibrations of damped oscillator forced by stochastic impulses - Jabłoński, M.; Ozga, A. (Archives of Acoustics, 2006)
Our theoretical study aims at finding some statistic parameters characterizing the vibrationsof an oscillator with damping and forced by stochastic impulses. We will derive thedependence of these parameters on rigidity and mass of the oscillator and on the stochasticdistribution of the impulse magnitude.We will also carry out a numerical simulation verifyingthe derived mathematical model and interpret the differences between the results obtained insimulation and the mathematical calculations.This study is the first stage of research aimed at designing a probe that will facilitate measuringparameters determining the quality of a technological process.